2021
DOI: 10.3389/fpsyt.2021.691251
|View full text |Cite
|
Sign up to set email alerts
|

Digital Shared Decision-Making Interventions in Mental Healthcare: A Systematic Review and Meta-Analysis

Abstract: Background: Shared decision-making (SDM) in mental healthcare has received increased attention as a process to reinforce person-centered care. With the rapid development of digital health technology, researchers investigate how digital interventions may be utilized to support SDM. Despite the promise of digital interventions to support SDM, the effect of these in mental healthcare has not been evaluated before. Thus, this paper aims to assess the effect of SDM interventions complimented by digital technology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…The study found a statistically significant difference in our primary outcome, patient activation, CHAI-MH (mean difference 4.39, 95% CI 0.99-7.79; Cohen d =0.33; P =.01), favoring the intervention group. These findings confirm our hypothesis that a digital SDM tool may promote patient activation by supporting the collaborative process between patients and their providers and is in concordance with recent meta-analyses on the effectiveness of digital SDM interventions that found these types of interventions to have an effect on patient activation [ 11 ]. The effect size (Cohen d ) for patient activation was 0.33, which may be interpreted as a small effect size.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study found a statistically significant difference in our primary outcome, patient activation, CHAI-MH (mean difference 4.39, 95% CI 0.99-7.79; Cohen d =0.33; P =.01), favoring the intervention group. These findings confirm our hypothesis that a digital SDM tool may promote patient activation by supporting the collaborative process between patients and their providers and is in concordance with recent meta-analyses on the effectiveness of digital SDM interventions that found these types of interventions to have an effect on patient activation [ 11 ]. The effect size (Cohen d ) for patient activation was 0.33, which may be interpreted as a small effect size.…”
Section: Discussionsupporting
confidence: 92%
“…Digital mental health interventions, such as interventions including a smartphone app, have been found to significantly outperform control groups [ 10 ]. However, the evidence on digital mental health interventions to support SDM is sparse, but a recent meta-analysis found that digital SDM interventions may have an effect on patient activation, decisional conflict, working alliance, and severity of general symptoms [ 11 ]. The meta-analysis also concluded that while digital interventions to support SDM are promising, the limited evidence is in need for quality research.…”
Section: Introductionmentioning
confidence: 99%
“…After the duplicate removal and screening of titles and abstracts, 25 full-text reviews were assessed for eligibility through full-text screening. After this assessment, 10 systematic reviews ( Broughton et al, 2021 ; Duncan et al, 2010 ; Fiorillo et al, 2020 ; Fisher et al, 2021 ; Légaré et al, 2018 ; Samalin et al, 2018 ; Stacey et al, 2017 ; Thomas et al, 2021 ; Vitger et al, 2021 ; Zisman-Ilani, Barnett et al, 2017 ) met the inclusion criteria ( Figure 1 ). All 10 reviews evaluated SDM interventions and/or tools for dyadic patient-clinician psychopharmacological decision-making and included various mental health conditions, SDM intervention types and outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…All reviews referred to the broader SDM literature and cited at least one of the following SDM models: Charles et al model of medical decision-making ( Duncan et al, 2010 ; Fisher et al, 2021 ; Légaré et al, 2018 ; Stacey et al, 2017 ; Thomas et al, 2021 ; Vitger et al, 2021 ; Zisman-Ilani, Barnett et al, 2017 ), the Integrative model of SDM ( Stacey et al, 2017 ), the Three Talk Model ( Broughton et al, 2021 ; Fiorillo et al, 2020 ; Légaré et al, 2018 ; Samalin et al, 2018 ; Vitger et al, 2021 ; Zisman-Ilani, Barnett et al, 2017 ), the SDM 3 Circle model ( Légaré et al, 2018 ; Vitger et al, 2021 ). However, not all reviews ( k = 9/10) included a definition of SDM ( Duncan et al, 2010 ; Fiorillo et al, 2020 ; Fisher et al, 2021 ; Légaré et al, 2018 ; Samalin et al, 2018 ; Stacey et al, 2017 ; Thomas et al, 2021 ; Vitger et al, 2021 ; Zisman-Ilani, Barnett et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Shared decision-making has received increased attention as a process to reinforce patient-centered care [ 15 ], and has been used in various diseases such as oncology and neonatology medicine [ 16 , 17 ]. It should be considered when controversial treatment divided clinicians’ opinion and the different treatments impact on the patient outcomes.…”
Section: Discussionmentioning
confidence: 99%